2014
DOI: 10.1590/1516-635x1604417-424
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal integrity and performance of broiler chickens fed a probiotic, a prebiotic, or an organic acid

Abstract: KeywordsScanning electron microscopy, morphometrics, intestinal mucosa, intestinal wall.Submitted: May/2013 Approved: February/2014 ABStRACt This study aimed at evaluating the intestinal integrity, using light and scanning electron microscopy (SEM), and the performance of broiler chickens fed additives alternative to antimicrobials. A total of 1080 male chicks were distributed according to a completely randomized experimental design, with six treatments with six replicates of 30 birds each. The following tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
4
15
1
2
Order By: Relevance
“…These findings agreed with Dizaji et al (2013), Fernandes et al, (2014) and Akoy (2015). They reported that FCR was low in all treated groups compared to the control group, and the lowest value was found for the synbiotic group.…”
Section: Effect Of Different Treatments Among Different Breeds On Prosupporting
confidence: 93%
See 1 more Smart Citation
“…These findings agreed with Dizaji et al (2013), Fernandes et al, (2014) and Akoy (2015). They reported that FCR was low in all treated groups compared to the control group, and the lowest value was found for the synbiotic group.…”
Section: Effect Of Different Treatments Among Different Breeds On Prosupporting
confidence: 93%
“…Concerning feed intake, the organic acid group of Cobb breed showed the highest value (3.87 kg), and the lowest value was found for the synbiotic group of Ross breed (3.65 kg). These results agreed with Akoy (2015) and Fernandes et al (2014). They found that feed amount was high in prebiotic and organic acid groups compared to the control group, while the lowest values were found in synbiotic and probiotic treated groups.…”
Section: Effect Of Different Treatments Among Different Breeds On Prosupporting
confidence: 91%
“…Mabelebele et al (2014) reported that the intestinal length of the broiler chicken with Ross strain 308 was 163.10 cm (duodenum 31.90 cm, jejunum 60.60 cm, and ileum 70.60 cm). The length of the small intestine found in this study was longer compared to the results of reported by Fernandes et al (2014) which observed that the length of small intestine of broiler chickens aged 42 days fed with several combinations of organic acids is 141.37 cm with a duodenal length 30.25 cm, jejunum 55.87 cm and ileum 55.25 cm. Meanwhile, the results of research by Adil et al (2011) reported a longer small intestine in broiler chickens fed with several types of organic acids than those fed without organic acids supplementation.…”
Section: Effect Of Treatment On Small Intestine Lengthcontrasting
confidence: 69%
“…And left breast meats, left leg meats, liver, and abdominal fat were weighed and expressed as the relative weight to live body weight. Production index (PI) was calculated by the following formula: PI = ((livability × average daily gain))/((feed conversion ratio × 10)) (Fernandes et al 2014).…”
Section: Samplingmentioning
confidence: 99%